Approach to the hydrodinamics of los vasquez lagoon (isla baril - colombian caribbean) by tanatocenosis of foramifera and bentonic ostracoda (1999)
Based on the study of the faunistic composition of tanatocenosis contained in superficial sediments as well as their origin, the currents affecting Los Vasquez lagoon, Isla Baru, (Colombian Caribbean) were deduced. The influence of the Caribbean current, the Panama countercurrent, the litoral drift and the local tidal currents is determined.